2006
DOI: 10.1007/bf02893413
|View full text |Cite
|
Sign up to set email alerts
|

Periacinar clefting and p63 immunostaining in prostatic intraepithelial neoplasia and prostatic carcinoma

Abstract: The aim of the present study was to correlate the presence and extent of retraction clefting and the expression of p63 in neoplastic glands and glands with prostatic intraepithelial neoplasia (PIN) in needle core biopsies.We analyzed needle core biopsies from 28 patients with PIN and 41 patients with adenocarcinoma. Neoplastic glands and those with PIN were analyzed on high power field (400x) and classified in three groups. Immunohistochemical staining was performed following Microwave Streptavidin ImmunoPerox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
13
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 25 publications
5
13
0
4
Order By: Relevance
“…We found that retractions are significantly more prominent in prostatic carcinoma, compared to PIN and non-neoplastic glands, in which they only occur sporadically [6,19]. These findings are consistent with previous assumption that clefting is associated with lack of basal cells and stromal changes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that retractions are significantly more prominent in prostatic carcinoma, compared to PIN and non-neoplastic glands, in which they only occur sporadically [6,19]. These findings are consistent with previous assumption that clefting is associated with lack of basal cells and stromal changes.…”
Section: Discussionsupporting
confidence: 92%
“…In our previous study, we analyzed periacinar retractions in p63 immunostained material of prostatic intraepithelial neoplasia (PIN) and prostatic carcinoma [19]. We found that retractions are significantly more prominent in prostatic carcinoma, compared to PIN and non-neoplastic glands, in which they only occur sporadically [6,19].…”
Section: Discussionmentioning
confidence: 97%
“…Dobijeni podaci idu u prilog činjenice da se periacinusne pukotine zaista mogu shvatiti kao važan pomoćni parametar u dijagnozi karcinoma prostate, za šta potvrda postoji i u literaturi [12,13,14,15,16,30]. …”
Section: Tabela 4 Stepen Neuroendokrine Diferencijacije U Adenokarciunclassified
“…U novijoj literaturi kao važan pomoćni dijagnostički kriterijum pominju se i periacinusne retrakcione pukotine [12,13,14,15,16,22,30].…”
unclassified
See 1 more Smart Citation